Developing a person-centered stated preference survey for dementia with Lewy bodies: value of a personal and public involvement process - Donnelly, Paula Sinead; Sweeney, Aoife; Wilson, Emily; Passmore, Anthony Peter; McCorry, Noleen K.; Boeri, Marco; Kane, Joseph P. M. (Frontiers in Dementia, 2024)
Introduction: The development of high-quality stated preference (SP) surveys requires a rigorous design process involving engagement with representatives from the target population. However, while transparency in the reporting of the development of SP surveys is encouraged, few studies report on this process and the outcomes. Recommended stages of instrument development includes both steps for stakeholder/end-user engagement and pretesting. Pretesting typically involves interviews, often across multiple waves, with improvements made at each wave; pretesting is therefore resource intensive. The aims of this paper are to report on the outcomes of collaboration with a Lewy body dementia research advisory group during the design phase of a SP survey. We also evaluate an alternative approach to instrument development, necessitated by a resource constrained context. Method: The approach involved conducting the stages of end-user engagement and pretesting together during a public involvement event. A hybrid approach involving a focus group with breakout interviews was employed. Feedback from contributors informed the evolution of the survey instrument. Results: Changes to the survey instrument were organized into four categories: attribute modifications; choice task presentation and understanding; information presentation, clarity and content; and best-best scaling presentation. The hybrid approach facilitated group brainstorming while still allowing the researcher to assess the feasibility of choice tasks in an interview setting. However, greater individual exploration and the opportunity to trial iterative improvements across waves was not feasible with this approach. Discussion: Involvement of the research advisory group resulted in a more person-centered survey design. In a context constrained by time and budget, and with consideration of the capacity and vulnerability of the target population, the approach taken was a feasible and pragmatic mechanism for improving the design of a SP survey.